KETERSEDIAAN DATA DALAM MENDUKUNG PEMANTAUAN DAN EVALUASI SMART CITY MATURITY (STUDI KASUS KOTA YOGYAKARTA) - Colleena, Marry; Djunaedi, Achmad (Jurnal Perencanaan dan Pengembangan Kebijakan, 2023)
The development of smart cities that have become a trend throughout the world, including Indonesia, requires a guideline in city development. Yogyakarta City is a city that has developed a smart city since the early 2000s which began with the existence of an information and complaint service unit (UPIK) as part of the implementation of open government. Active people in Yogyakarta City who access Jogja Smart Services (JSS) are only 6.5% of the total population, so it shows that human relations in the JSS application have not been carried out properly. The government through SNI 37122:2019 applies variables and indicators as well as data needs needed to assess the level achievement of smart cities. This paper aims to explain the availability of data and identify data that is not available in Yogyakarta City based on SNI 37122:2019 also how strategies to complete the data. The method used in this study uses a qualitative approach. The availability of data in the government of Yogyakarta consists of 118 data, data found elsewhere other than the city government is 13% and no data anywhere is 25 data. The strategy to enrich the data is through proper policies, technology infrastructure, and application development.